A Mirror to Nature : Transformations in Drama and Aesthetics 1660-1732 - Zimbardo, Rose A. (Book collections on Project MUSE., 1986)
In this provocative study Rose Zimbardo examines a crucial revolution in aesthetics that took place in the late seventeenth century and that to this day dominates our response to literature. Although artists of that time continued to follow the precept ""imitate nature, "" that nature no longer corresponds to the earlier understanding of the term. What had been in essence an allegorical mode came to be a literal one. Focusing on the drama of the period as an exemplary form, Zimbardo shows how it moved from depicting a metaphysical reality of idea to portraying an inner reality of individual expe.